Are economics a key to dating Urdeuteronomium? A response to Sandra Lynn Richter. (September 2020) - Berge, Kåre; Edelman, Diana; Guillaume, Philippe; Rossi, Benedetta
While welcoming Sandra Richter's suggestion in a recent Journal for the Study of the Old Testament article that economics should be integrated in the study of Deuteronomy, a number of points in her argument to date Urdeuteronomium in the Iron Age I–II transition are inaccurate or based on contestable assumptions and arguments from silence.